Project-Based Teaching Modules for Character Formation: A Case Study of the Pancasila Student Profile Program in Elementary School: Modul Pembelajaran Berbasis Proyek untuk Pembentukan Karakter: Studi Kasus Program Profil Siswa Pancasila di Sekolah Dasar - Novia Ramadhani Budianingsih; Mahardika Darmawan Kusuma Wardana (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The implementation of the Merdeka Curriculum in Indonesia emphasizes character education through the Pancasila Student Profile Strengthening Project (P5) in elementary schools. Specific Background: Teaching modules function as key instructional tools that guide teachers in organizing project-based learning activities integrating collaboration, caring, and sharing values. Knowledge Gap: Empirical evidence describing how teachers practically implement these modules to cultivate mutual cooperation in real classroom contexts remains limited. Aims: This study analyzes the implementation of teacher teaching modules in the P5 mutual cooperation project at SDN Ketajen 1 using a qualitative case study. Results: Data from observation, interviews, and documentation indicate that learning activities were interactive, inspiring, enjoyable, challenging, and motivating, with high implementation scores across indicators, while small-group projects such as ecoprint facilitated communication, collaboration, empathy, and active participation, although some students remained passive. Novelty: The study provides a contextual description of module-based project learning that systematically integrates social character values through structured classroom practices. Implications: Findings offer practical guidance for teachers and schools to design student-centered modules and professional development programs that strengthen character formation and meaningful learning within elementary education. Keywords: Teaching Modules, P5 Project, Mutual Cooperation, Character Education, Elementary School Key Findings Highlights: Small-group projects fostered peer support and shared responsibility Classroom activities recorded consistently high implementation indicators above ninety percent Structured lesson design encouraged initiative and independent problem solving